1999
DOI: 10.1111/j.1530-0277.1999.tb04127.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Ethanol Sensitivity and Tolerance Development in γ‐Protein Kinase C Null Mutant Mice Is Dependent on Genetic Background

Abstract: Initial sensitivity and tolerance development to the sedative-hypnotic and hypothermic effects of ethanol were investigated in gamma-protein kinase C (PKC) null mutant mice. Null mutants from a C57BL/6J x 129/SvJ mixed genetic background demonstrated decreased ethanol sensitivity and failed to develop chronic tolerance after 10 days of ethanol liquid diet. However, when the null mutation was introgressed onto a C57BL/6J background for six generations, the "no tolerance" phenotype for sedative-hypnotic and hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…These modifier genes are often completely unlinked to the targeted locus but are closely related to its function. For example, mice null for ␥-protein kinase C showed a marked difference in sensitivity and tolerance to ethanol solely depending on the genetic background (11). This issue is compounded by the desired intercrossing of several modified lines which may have been generated on genetically distinct backgrounds.…”
Section: Conventional Germ Line Gene-targetingmentioning
confidence: 99%
“…These modifier genes are often completely unlinked to the targeted locus but are closely related to its function. For example, mice null for ␥-protein kinase C showed a marked difference in sensitivity and tolerance to ethanol solely depending on the genetic background (11). This issue is compounded by the desired intercrossing of several modified lines which may have been generated on genetically distinct backgrounds.…”
Section: Conventional Germ Line Gene-targetingmentioning
confidence: 99%
“…This breeding strategy produces homozygous mutant, heterozygous, and homozygous wild-type genotypes within a single litter, thereby providing wild-type littermate controls for each experiment. The PKCγ mutation is maintained in a heterozygous condition on C57BL/6 and 129/S6 inbred strains because homozygous null mutant mice do not survive on the C57BL/6 background (Bowers et al, 1999). All mice were genotyped prior to testing using DNA analysis of tail DNA as described previously (Bowers and Wehner, 2001).…”
Section: Animalsmentioning
confidence: 99%
“…Bowers et al (Bowers et al, 1999) found that the impact of a null mutation of the γ-protein kinase C gene on initial sensitivity to ethanol was modulated by the background genotype of the mouse strain examined. In some strains, the "no tolerance" phenotype was expressed as expected while in other strains, the "no tolerance" phenotype was not expressed.…”
Section: Introductionmentioning
confidence: 99%